2018
DOI: 10.1007/s10212-018-0387-8
|View full text |Cite
|
Sign up to set email alerts
|

Links between socio-emotional skills, behavior, mathematics and literacy performance of preschool children in Serbia

Abstract: Young children's socio-emotional skills are important for understanding their own and other's behaviours and interactions. No study in Serbia has investigated this before. In this study we explored the links between early socio-emotional skills, behaviour, and mathematics and literacy performance of preschool children in Serbia over time. Children (N = 159) aged 5-8 were rated by the teachers on their socio-emotional skills and behaviour, and their literacy and mathematics assessed at three-time points over 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
(71 reference statements)
1
4
0
2
Order By: Relevance
“…The model that included the indicator for PSED for language skills was the best adjusted (R²) and had an effect size larger than the coefficients of behavior indicators and variables widely studied and discussed within the educational field, such as the SES of the family unit. This difference shows the importance of social and emotional skills, as increasingly reported in the literature (ALEKSIC, 2019;ALMLUND et al, 2011;(HECKMAN;STIXRUD;URZUA, 2006). Once again, what is noteworthy in the results presented is the age bracket studied (children enrolled in pre-school) and the consistency of the results when compared with other findings in national and international studies that reinforce an association between social and emotional skills and cognitive development (CASEL, 2015;PRIMI, 2014).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The model that included the indicator for PSED for language skills was the best adjusted (R²) and had an effect size larger than the coefficients of behavior indicators and variables widely studied and discussed within the educational field, such as the SES of the family unit. This difference shows the importance of social and emotional skills, as increasingly reported in the literature (ALEKSIC, 2019;ALMLUND et al, 2011;(HECKMAN;STIXRUD;URZUA, 2006). Once again, what is noteworthy in the results presented is the age bracket studied (children enrolled in pre-school) and the consistency of the results when compared with other findings in national and international studies that reinforce an association between social and emotional skills and cognitive development (CASEL, 2015;PRIMI, 2014).…”
supporting
confidence: 67%
“…A longitudinal study performed in Serbia using PIPS methodology with 159 children aged between 5 and 8, found that the social skills section of PSED, measured at 5 years of age, could be a predictor of literacy skills at the age of 8 (B = 0.29), while controlling for gender and maternal Education (ALEKSIC et al, 2019).…”
Section: The Relationship Between Socioeconomic Development Behavior and Cognitive Developmentmentioning
confidence: 99%
“…Estas incluyen ayudar, compartir y colaborar. La relación encontrada entre ALAIH y prosocialidad a los tres años de edad (Wirth et al, 2020), sugiere la relevancia de las conductas prosociales para la generación de actividades conjuntas con adultos con potencial de aprendizaje (Aleksić et al, 2019).…”
Section: Conductas Prosocialesunclassified
“…They include helping, sharing and collaborating. The relation detected between HLLE and prosociality at the age of three (Wirth et al, 2020) suggests the importance of prosocial behaviours in generating joint activities with adults with the potential for learning (Aleksić et al, 2019).…”
Section: Factors Associated With Home Literacy Environment Groupsmentioning
confidence: 99%
“…O processo de aprendizado em algumas áreas da educação como a educação financeira (Peeters et al, 2018) (Compen et al, 2019), matemática (Aleksic et al, 2018) e educação alimentar (Ronto et al, 2016) tem demonstrado certas fragilidades e resultados educacionais aquém do esperado. Isso provavelmente ocorre pelo fato de que boa parte das intervenções focam quase que exclusivamente no ensino de conhecimento, com distanciamento do que ocorre na realidade.…”
Section: Introductionunclassified